PENGEMBANGAN BAHAN AJAR ETNOMATEMATIKA DIALEK KHAS TEGAL BERBASIS DIGITAL PADA SEKOLAH DASAR - Ashila Yumna, Asma'; Setiyadi, Desi; Nida Fitriyani, Feny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning at the elementary school level still faces several challenges, particularly because the instructional materials used tend to be abstract and have not integrated the local cultural context close to students' lives. This condition has implications for students' low understanding of mathematical concepts and declining interest in learning. This study aimed to develop digital learning materials based on ethnomathematics that utilize the distinct Tegal dialect in elementary school mathematics learning to produce a valid and feasible product. The method applied was Research and Development (R&D) using the ADDIE model, which includes the phases of analysis, design, development, implementation, and evaluation. The study involved 22 first-grade students at KLS Elementary School in Tegal Regency as the research subjects. Data collection was conducted through observation, documentation, and expert validation questionnaires, while data analysis used descriptive quantitative techniques based on the percentage of product feasibility. The development results showed that the ethnomathematics-based mathematics e-module with the Tegal dialect, which integrates local number vocabulary such as siji, loro, and telu, achieved a highly feasible category. This was indicated by the validation results of 100% from the material expert, 96.88% from the language expert, and 96% from the media expert. Furthermore, the learning evaluation results showed a student average score of 94.32, with a highest score of 100 and a lowest score of 80, and a classical mastery rate reaching 100% of all students who took the evaluation. These findings indicate that the developed e-module is capable of supporting the understanding of addition and subtraction concepts while integrating local cultural elements into the mathematics learning process. Thus, the implementation of local culture-based ethnomathematics in digital learning materials has the potential to be an innovative alternative to improve the quality of mathematics learning while supporting efforts to preserve regional culture in elementary schools.